Immune Function following Major Spinal Surgery and General Anesthesia - Relland, Lance M.; Hall, Mark; Martin, David P.; Nateri, Jyotsna; Hanson-Huber, Lisa; Beebe, Allan; Samora, Walter; Klamar, Jan; Muszynski, Jennifer; Tobias, Joseph D. (Journal of Pediatric Intensive Care, 2020)
There are reported differences in the effects that general anesthetics may have on immune function after minor surgery. To date, there are no prospective trials comparing total intravenous anesthesia (TIVA) with a volatile agent-based technique and its effects on immune function after major spinal surgery in adolescents. Twenty-six adolescents undergoing spinal fusion were randomized to receive TIVA with propofol-remifentanil or a volatile agent-based technique with desflurane-remifentanil. Immune function measures were based on the antigen-presenting and cytokine production capacity, and relative proportions of cell populations. Overall characteristics of the two groups did not differ in terms of perioperative times, hemodynamics, or fluid shifts, but those treated with propofol had lower bispectral index values. Experimental groups had relatively high baseline interleukin-10 values, but both showed a significant inflammatory response with similar changes in their respective immune functions. This included a shift toward a granulocytic predominance; a transient reduction in monocyte markers with significant decrease in antigen-presenting capacity and cytokine production capacity. Anesthetic choice does not appear to differentially impact immune function, but exposure to anesthetics and surgical trauma results in reproducibly measurable suppression of both innate and adaptive immunity in adolescents undergoing posterior spinal fusion. The magnitude of this suppression was modest when compared with pediatric and adult patients with critical illnesses. This study highlighted the need to evaluate immune function in a broader population of surgical patients with higher severity of illness.
Keywords: anesthesia; spinal fusion; immunity; immune suppression; cytokine; trauma